Neoliberalism and changing role of the state in low cost housing provision in Malaysia - Shuid, Syafiee (2011)
Over the last two decades, neoliberalism has dominated housing policy discourse, formulation and implementation in many East Asian countries particularly since the Asian Financial Crisis in 1997-1998. However the neoliberal transformation remained uneven between countries. There are continuous debates on the adoption and rejection of neoliberal housing policies in many East Asian countries. In the context of Malaysia, the market had played significant role in low cost housing provision since 1990s with the state began to retreat in direct housing provision. However the trend towards market provision suddenly disrupted by the financial crisis. Despite the pressure from international agencies particular IMF for neoliberal reform during the crisis, the state began to embark on large scale public housing provision for rental known as People Housing Programme (PHP) in 1998. With the house monthly rental well below the market rate and direct provision by the state, the programme clearly against the neoliberal policy. Thus, the paper will discuss the changing role of the state in low cost housing provision in Malaysia in the post crisis era in the context of neoliberalism debates. The political economy and leadership changes in Malaysia since 1998 which clearly have significant impact towards the role of the state in low cost housing provision will also highlighted in the paper. Thus, contribute to wider debates on neoliberal transformation in housing provision in East Asia.